ETHNOBOTANICAL STUDY OF TWO MEDICINAL PLANTS: VITEX AGNUS CASTUS and ANABASIS ARETIOIDES - Berrani, Assia; LRHORFI, L Aicha; LARBI, Ouahidi My; ZOUARHI, Meryem; Lella, Ould Abdellahi; BOUFELLOUS, Moncef; BENGUEDDOUR, Rachid (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
In the context of the valorization of medicinal and aromatic plants of the Moroccan and Saharan flora, we were interested on the ethnobotanical study of two species often used by the population: Vitex agnus castus of the verbenaceas family, commonly called kharwa¢ and Anabasis aretioids of the family of chenopodeaceae, commonly called Shejra li maidihach errih. For example, a series of ethnobotanical surveys was carried out in 2015, using a questionnaire, in three regions (Meknes Tafilalet, Gharb Chrarda Bni Hssen, and Rabat Sale Zemmour Zaer) Traditional herbalists and druggists in order to know the medicinal virtues of these two plants. The results of the study showed that the leaves are the most used part of these 2 plants and the majority of the remedies are prepared in the form of decoction for Anabasis and in powder form for Vitex. On the whole of the diseases treated by these two plants, the affections of the digestive tubes occupy the first place with a rate of 27.67%, followed by the antidotes of poison 20.67% for Anabasis, and then to the genitourinary affections occupy the first place with 46.67% followed by dermatology affections with 20%. Keywords: Vitex agnus castus, Anabasis aretio¯des, Ethnobotanical, survey, Traditional medicine.